2012
DOI: 10.3390/e14060993
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Automata on Graphs: Topological Properties of ER Graphs Evolved towards Low-Entropy Dynamics

Abstract: Cellular automata (CA) are a remarkably efficient tool for exploring general properties of complex systems and spatiotemporal patterns arising from local rules. Totalistic cellular automata, where the update rules depend only on the density of neighboring states, are at the same time a versatile tool for exploring dynamical processes on graphs. Here we briefly review our previous results on cellular automata on graphs, emphasizing some systematic relationships between network architecture and dynamics identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Such cellular automata on graphs are a well established method for probing the relationship between network architecture and dynamics (see, e.g., [20,23,24]). It is clear that discrete models need to be used with a certain care, as some dynamical effects can indeed be artifacts of the (time and state) discretizations.…”
Section: Introductionmentioning
confidence: 99%
“…Such cellular automata on graphs are a well established method for probing the relationship between network architecture and dynamics (see, e.g., [20,23,24]). It is clear that discrete models need to be used with a certain care, as some dynamical effects can indeed be artifacts of the (time and state) discretizations.…”
Section: Introductionmentioning
confidence: 99%
“…The article discusses implications in the context of information transmission in complex network systems. As presented in Reference [76], CA on graphs are a parameter-efficient framework for exploring the relationship between network architecture and dynamics from the perspective of pattern In Reference [77], O'Sullivan presented a new type of dynamic spatial model. The author showed that a graph-CA with specified structural properties that are defined by the relationships between the subsets of cells is a very useful generalisation of the classical CA.…”
Section: Information-spreading Modelling With Cellular Automata and Gmentioning
confidence: 99%
“…In the last decade, the fusion of networks and cellular automata, appeared into the Literature [17][18][19][20]. This discrete dynamical system, called as Network Automata (NA), uses the network structure as the tessellation of the cellular automaton, whose dynamics is governed by a rule that defines the states of its nodes at each time step.…”
Section: Introductionmentioning
confidence: 99%